1988
DOI: 10.1002/jor.1100060215
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic resistance: A measure of vascular outflow obstruction in osteonecrosis

Abstract: This study introduces hydraulic resistance (HR) as a new method to measure intraosseous vascular outflow resistance in the human proximal femur. HR is the standard measure of resistance to fluid flow in porous matrices and is derived from serial pressure/flow determinations. Eighteen hips were studied in 11 patients taken to surgery for core decompression therapy of presumable atraumatic osteonecrosis of the femoral head. HR was much higher in osteonecrotic (174 +/- 29 mm Hg min/ml, SE) than in normal human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The femoral head is at an especially high risk of ischemic in-jury because of the absence of an effective collateral circulation [Downey et al, 1988]. Although different risk factors have been found that could lead to the disruption of the vascular supply, and several theories have been proposed and discussed elsewhere in detail [Lavernia et al, 1999;Assouline-Dayan et al, 2002], precise mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The femoral head is at an especially high risk of ischemic in-jury because of the absence of an effective collateral circulation [Downey et al, 1988]. Although different risk factors have been found that could lead to the disruption of the vascular supply, and several theories have been proposed and discussed elsewhere in detail [Lavernia et al, 1999;Assouline-Dayan et al, 2002], precise mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the absence of an effective collateral circulation, which could compensate for the severing of the primary blood supply, the femoral head is at an especially high risk of ischemic injury. 13…”
mentioning
confidence: 99%
“…Irrespective of where the blood flow is initially disrupted, i.e. at the level of arteries, veins, capillaries or sinusoids, the circulation in the arteries is ultimately arrested [3]. …”
Section: Introductionmentioning
confidence: 99%